Peran Guru PAI Dalam Meningkatkan Kecerdasan Spiritual Siswa SMP Takhassus Al-Qur’an Kalibeber Wonosobo - Indra Lesmana; Sri Haryanto; Salis Irvan Fuadi (Jurnal Manajemen dan Pendidikan Agama Islam, 2024)
This research aims to reveal the role of Islamic religious education teachers in increasing the spiritual intelligence of students at Takhassus Al-Qur'an Middle School, Kalibeber. This research uses a descriptive qualitative research approach. The subject of this research is an Islamic religious education teacher. Data collection techniques use observation, interviews and documentation methods. Data sources were obtained from primary data sources, namely PAI teachers, school principals, and students, as well as secondary data sources, namely books and journals. The data analysis technique uses data reduction steps, data presentation and drawing conclusions. The results of the research show that students at Takhassus Al-Qur'an Kalibeber Middle School are good at practicing spiritual intelligence both in the school environment and outside of school. This can be seen when the teacher takes the role of teacher in class, students are expected to be polite when the teacher explains the material. Therefore, this attitude has a positive impact on students because they are used to being polite to the people around them.